2017
DOI: 10.1080/10428194.2017.1300888
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of peripheral T-cell lymphoma in first complete remission: a Danish-Swedish population-based study

Abstract: In the present study, we investigate the outcome of 109 Danish and 123 Swedish patients with nodal PTCL in first complete remission (CR), and examine the impact of imaging-based follow-up (FU) strategies. The patients were selected by the following criteria: (a) newly diagnosed nodal PTCL from 2007 to 2012, (b) age ≥18 years, and (c) CR after CHOP or CHOEP therapy. FU guidelines in Sweden included symptom assessment, clinical examinations and blood tests at 3-4-month intervals for 2 years. FU strategies in Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The databases across the variables described are remarkably concordant, and even the OS curves of the populations are similar to that described from other international registries (17,18). First, the data confirm that those patients receiving pralatrexate earlier exhibit superior benefit as measured by ORR, CR, DOR, and PFS.…”
Section: Discussionsupporting
confidence: 73%
“…The databases across the variables described are remarkably concordant, and even the OS curves of the populations are similar to that described from other international registries (17,18). First, the data confirm that those patients receiving pralatrexate earlier exhibit superior benefit as measured by ORR, CR, DOR, and PFS.…”
Section: Discussionsupporting
confidence: 73%
“…While clinical assessment is required, there is a lack of evidence to support routine imaging surveillance of BIA-ALCL whether limited or advanced stage. 86,87 This is analogous to the clinical principles that guide surveillance in other NHL subtypes, that routine imaging does not improve patient outcomes. [88][89][90] Our recommendation takes into consideration evidence from a range of lymphoma subtypes, the American Society of Hematology Choosing Wisely Campaign 91 and surveillance guidance provided by the NICE guidelines on NHLs.…”
Section: Ongoing Surveillancementioning
confidence: 96%
“…We advocate joint patient follow‐up between the surgical and haemato‐oncology teams every 3–6 months, for a minimum of two years and then as indicated. While clinical assessment is required, there is a lack of evidence to support routine imaging surveillance of BIA‐ALCL whether limited or advanced stage 86,87 . This is analogous to the clinical principles that guide surveillance in other NHL subtypes, that routine imaging does not improve patient outcomes 88–90 .…”
Section: Clinical Presentation and Investigationmentioning
confidence: 99%
“…The results have been mixed; some studies have reported trends toward better outcomes, but most have not 7,8,10,17 . Other types of studies have compared survival outcomes in large patient populations exposed to different disease surveillance strategies and found comparable outcomes with or without imaging 6,18 …”
mentioning
confidence: 99%